Патогенетичне значення антимікробних пептидів у реалізації антибактеріального захисту у дітей, хворих на муковісцидоз - Леженко, Геннадій Олександрович; Абатуров, Олександр Євгенович; Пашкова, Олена Єгорівна; Пантюшенко, А. І.; Леженко, Г. А.; Абатуров, А. Е.; Пашкова, Е. Е.; Пантюшенко, А. И.; Lezhenko, G. O.; Abaturov, O. Ye.; Pashkova, O. Ye.; Pantyushenko, L. I. (My University, 2013)
Обстежено 37 дітей, хворих на муковісцидоз, віком від 3 до 15 років. Контрольну групу становили 30 здорових дітей. Встановлено, що дітям, хворим на муковісцидоз, притаманне підвищення вмісту в плазмі крові а-дефензинів 1—3, продукція яких адаптивно підвищувалася у відповідь на контамінацію дихальних шляхів Рs.aeruginosa. Високі концентрації дефензинів пригнічували фагоцитарну активність нейтрофілів, унаслідок чого компенсаторно-адаптаційна реакція, спрямована на подолання контамінації патогену, набувала характеру патологічної і виступала додатковим фактором ураження дихальної системи. Інфікування хворих на муковісцидоз Ps.aeruginosa приводило до порушення перебігу другої фази запалення за рахунок відсутності адекватної активації іNOS. У відповідь на зниження генерації оксиду азоту у дітей, хворих на муковісцидоз, інфікованих Рs.aeruginosa, відбувалося підвищення рівня NTproBNP у сироватці крові, що є компенсаторною реакцією і може виступати додатковим фактором підтримки хронічного запалення та ураження дихальної системи. Обследовано 37 детей, больных муковисцидозом, в возрасте от 3 до 15 лет. Контрольную группу составили 30 здоровых детей. Установлено, что детям с муковисцидозом присуще повышение содержания в плазме крови а-дефензинов 1—3, продукция которых адаптивно повышалась в ответ на контаминацию дыхательных путей Рs.aeruginosa. Высокие концентрации дефензинов угнетали фагоцитарную активность нейтрофилов, вследствие чего компенсаторно-адаптационная реакция, направленная на преодоление контаминации патогена, принимала характер патологической и являлась дополнительным фактором поражения дыхательной системы. Инфицирование больных муковисцидозом Рs.aeruginosa приводило к нарушению течения второй фазы воспаления за счет отсутствия адекватной активации іNOS. В ответ на снижение генерации оксида азота у детей с муковисцидозом, инфицированных Рs.aeruginosa, происходило повышение уровня NTproBNP в сыворотке крови, что является компенсаторной реакцией и может быть дополнительным фактором поддержания хронического воспаления и поражения дыхательной системы. Objective: to investigate the factors increasing the colonization of respiratory system with Ps.aeruginosa in children with cystic fibrosis. Materials and methods. The study involved 37 children with cystic fibrosis at the age from 3 to 15 years. The control group consisted of 30 healthy children. The results of the bacteriological examination of sputum were evaluated. The plasma levels of a-defensins 1—3 (HNP 1—3), serum levels of C-reactive protein (CRP), metabolites of nitric oxide (NO), inducible NO-synthase (iNOS), NTproBNP were investigated. Results. According to the results of bacteriological examination of sputum pathogens was identified in 22 (59.4 %) patients. The dominant microorganisms were presented by Ps.aeruginosa in 14 (37.8 %) patients. Patients with cystic fibrosis have had 3.9 times increased levels of HNP 1—3 in plasma in comparison with control group (p < 0.05). The presence of Ps.aeruginosa led to the 6.8 times increase of HNP 1—3 in plasma of children with cystic fibrosis (p < 0.001). Simultaneously, the presence of Ps.aeruginosa resulted in an increase of CRP (p < 0.01). Contamination of the patients with cystic fibrosis by Ps.aeruginosa contributed to lack of NO and iNOS production. Colonization of the lower respiratory tract by Ps.aeruginosa associated with 1.7 times increased levels of NTproBNP in comparison with control group (p < 0.05). Conclusions: 1. Children with cystic fibrosis had been characterized by elevation of plasma level of a-defensins 1—3. Production of HNP 1—3 adaptively increased in response to the contamination of the respiratory tract by Ps.aeruginosa, but high concentration of a-defensins 1—3 depressed phagocytic activity of neutrophils. Under such conditions compensatory-adaptive response, that was intended at the overcoming of pathogenic contamination, take a turn of pathologic and was an additional factor of respiratory system affection. 2. In children with cystic fibrosis reduction of generation of nitric oxide regardless of the microbial status of respiratory system took place. Availability of Ps.aeruginosa in respiratory system microbiota assisted to the adequate course of the second phase of inflammation at the expense of absence of iNOS adequate activation. 3. Increased serum level of NTproBNP in children with cystic fibrosis, infected with Ps.aeruginosa, is a compensatory reaction in response to the activation of endothelin-1 synthesis and serves as additional factor of supporting of chronic inflammation and damage of the respiratory system.
Патогенетическое значение антимикробных пептидов в реализации антибактериальной защиты у детей, больных муковисцидозом
Pathogenetic significance of antimicrobial peptides in the implementation of antibacterial protection in children with cystic fibrosis
Keywords: муковісцидоз; а-дефензини 1-3; оксид азоту; іNOS NTproBNP; Рs.aeruginosa; муковисцидоз; а-дефензины 1-3; оксид азота; cystic fibrosis; defensins 1—3; nitric oxide